Institutional Antecedents of Partnering for Social Change: How Institutional Logics Shape Cross-Sector Social Partnerships - Vurro, Clodia (Journal of business ethics, 2010)
Heeding the call for a deeper understanding of how cross-sector social partnerships (CSSPs) can be managed across different contexts, this article integrates ideas from institutional theory with current debate on cross-boundary collaboration. Adopting the point of view of business actors interested in forming a CSSP to address complex social problems, we suggest that “appropriateness” needs shape business approaches toward partnering for social change, exerting an impact on the benefits that can be gained from it. A theoretical framework is proposed that identifies and frames four CSSP styles, as resulting from combinations of dominant institutional orientations in a field and its general level of coherence. We show how, depending on prevailing institutional logics, intervention models underlying the CSSP have to emphasize either the business soundness of the initiative or its social value, together with a consistent leadership style. Moreover, while directive approaches based on concentrated governance structures aimed at setting the rules of the game are shown to prevail in fields characterized by low level of institutional coherence, participative models emerge in more established fields, with CSSP’s promoter playing an integrative role through distributed governance structures. The article concludes with a summary and implications of an institutional-based view of CSSPs.